2019
DOI: 10.1111/jcpp.13042
|View full text |Cite
|
Sign up to set email alerts
|

Alpha modulation during working memory encoding predicts neurocognitive impairment in ADHD

Abstract: Background Attention‐deficit/hyperactivity disorder (ADHD) is associated with working memory (WM) deficits. However, WM is a multiprocess construct that can be impaired through several pathways, leaving the source of WM impairments in ADHD unresolved. In this study, we aim to replicate, in an independent sample, previously reported deficits in component processes of WM deficits in ADHD and expand to consider their implications for neurocognitive outcomes. Methods In 119 children (7–14 years old, 85 with ADHD),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 43 publications
2
56
1
Order By: Relevance
“…Given that this response typically increases in amplitude with the difficulty of a task, it is possible that at the same level of difficulty, CHL required a higher level of suppression or inhibition in order to properly maintain the stimulus. Interestingly, increases in maintenance-related alpha ERS responses during working memory processing have also been found in ADHD and other related attention disorders ( Lenartowicz et al, 2019 , Missonnier et al, 2013 ); thus, it is possible that this elevation in CHL may be related to altered attention function. Behaviorally speaking, CHL have been shown to be diagnosed with ADHD at higher rates than CNH ( Soleimani et al, 2020 , Theunissen et al, 2014a ), though the literature is relatively variable (see ( Theunissen et al, 2014b )).…”
Section: Discussionmentioning
confidence: 98%
“…Given that this response typically increases in amplitude with the difficulty of a task, it is possible that at the same level of difficulty, CHL required a higher level of suppression or inhibition in order to properly maintain the stimulus. Interestingly, increases in maintenance-related alpha ERS responses during working memory processing have also been found in ADHD and other related attention disorders ( Lenartowicz et al, 2019 , Missonnier et al, 2013 ); thus, it is possible that this elevation in CHL may be related to altered attention function. Behaviorally speaking, CHL have been shown to be diagnosed with ADHD at higher rates than CNH ( Soleimani et al, 2020 , Theunissen et al, 2014a ), though the literature is relatively variable (see ( Theunissen et al, 2014b )).…”
Section: Discussionmentioning
confidence: 98%
“…In others, auditory selective attention task, larger theta (Yordanova et al, 2006) and reduced mu (Yordanova et al, 2013) evoked by irrelevant (non-targets, non-attended) stimuli were reported. The alpha oscillation presented an attenuated event-related desynchronization (ERD) during the encoding phase and an increased occipital power spectrum during the maintenance phase of a spatial working memory task performed by ADHD children (Lenartowicz et al, 2019). In these patients, an increased parieto-occipital gamma band evoked during the encoding phase of a recognition test (Lenz et al, 2008) that did not correlate with performance (Lenz et al, 2008) or differentiate between the known and unknown items (Lenz et al, 2010) was reported.…”
Section: Introductionmentioning
confidence: 97%
“…Maintenance, Interference control), due to high overlap in the elements contained within each subconstruct and difficulty in distinguishing them in empirical studies. A primary link with the Disinhibited Externalizing spectrum and Substance Abuse subfactor is supported by associations of markers of behavioral and paradigms units of analysis with inattentive and hyperactive-impulsive symptoms (Lenartowicz et al, 2019;Michelini et al, 2018;Müller et al, 2015;Polner et al, 2015) and with substance use escalation (Khurana et al, 2013;Peeters et al, 2014;Squeglia et al, 2014), captured by the Substance Abuse subfactor. Similar associations with externalizing problems further suggest a primary link to the Antisocial Behavior subfactor (Agnes Brunnekreef et al, 2007;Huang-Pollock et al, 2017).…”
Section: Working Memorymentioning
confidence: 99%